Análisis de riesgos de la infraestructura de red de la Universidad Técnica de Machala, basado en la norma ISO/IEC 27005:2008 y propuesta de un plan de gestión - Rojas Vilela, Lila Katherine (2014)
This Thesis was developed in the unit system of the Technical University of Machala comprising a risk analysis of network infrastructure specifically to the core layer, based on ISO / IEC 27005: 2008.